Regime types and winner-loser Gaps in support for democracy in East Asia. Issue 6 (18th August 2022) - Wu, Chun-Ying; Wu, Chin-en
ABSTRACT: What is the effect of regime type on democratic support among political winners and losers? Existing studies on the winner-loser gap in political attitudes mostly discuss satisfaction with democracy and political trust without testing the conditional effect of political regimes. We argue that because winners and losers have different understandings of the word "democracy, " support for democracy as an ideal political system is not a valid measurement of democratic support in autocracies. In this article, we examine support for liberal democratic values in different regime types. We find a clear winner-loser gap in competitive authoritarian regimes since supporters of the ruling parties are less enthusiastic about democratic principles that would constrain executive power than those who support the opposition. In democracies, this gap is much smaller as all voters may become political underdogs after free and fair elections; both winners and losers prefer civil liberties and limited executive power, therefore they uphold democratic values at similar levels. We test our argument using four waves of the Asian Barometer Survey.